2011
DOI: 10.1016/j.coviro.2011.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule studies of viral DNA packaging

Abstract: Assembly of many dsDNA viruses involves packaging of DNA molecules into pre-assembled procapsids by portal molecular motor complexes. Techniques have recently been developed using optical tweezers to directly measure the packaging of single DNA molecules into single procapsids in real time and the forces generated by the molecular motor. Three different viruses, phages phi29, lambda, and T4, have been studied, revealing interesting similarities and differences in packaging dynamics. Single-molecule fluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 50 publications
1
58
0
Order By: Relevance
“…At a given external osmotic pressure, by varying the salinity of solution, one can also vary the amount of DNA ejected. Interestingly, it has been shown that monovalent counterions such as NaCl have a negligible effect on the DNA ejection process [3,12,13]. In contrast, multivalent counterions such as Mg +2 , CoHex +3 (Co-hexamine), Spd +3 (spermidine) or Spm +4 (spermine) exert strong effect, both qualitatively and quantitatively different from that of monovalent counterions.…”
Section: Introductionmentioning
confidence: 98%
“…At a given external osmotic pressure, by varying the salinity of solution, one can also vary the amount of DNA ejected. Interestingly, it has been shown that monovalent counterions such as NaCl have a negligible effect on the DNA ejection process [3,12,13]. In contrast, multivalent counterions such as Mg +2 , CoHex +3 (Co-hexamine), Spd +3 (spermidine) or Spm +4 (spermine) exert strong effect, both qualitatively and quantitatively different from that of monovalent counterions.…”
Section: Introductionmentioning
confidence: 98%
“…Phage terminases are among the strongest and fastest known molecular machines. 35 The T4 packaging motor has an average translocation speed of ~700 bp/sec, and can achieve rates as high as 2000 bp/sec. 35,36 The motor can exert forces larger than 60 pN to overcome the pressure generated inside the capsid by the packaged DNA.…”
Section: Capsid Assemblymentioning
confidence: 99%
“…These molecular motors can work against a force larger than 50 pN and package DNA at high rates, placing them among the most powerful molecular motors in nature (9,11). Most phage DNA packaging motor proteins are bifunctional enzymes that integrate two types of enzymatic activities, the ATPase and the nuclease, as required by the concatemeric nature of the packaging substrates.…”
mentioning
confidence: 99%